LEOPARD Syndrome with PTPN11 Gene Mutation in Three Family Members Presenting with Different Phenotypes - Alfurayh, Nuha; Alsaif, Fahad; Alballa, Nouf; Zeitouni, Leena; Ramzan, Khushnooda; Imtiaz, Faiqa; Alakeel, Abdullah (Journal of Pediatric Genetics, 2020)
LEOPARD syndrome (LS) is a rare autosomal dominant disorder that is characterized by multiple lentigines and various congenital anomalies. The clinical diagnosis of LS requires molecular confirmation. The most frequently reported mutations in LS patients are in the protein tyrosine phosphatase nonreceptor type 11 gene, PTPN11. Herein, we report the cases of three family members from two generations who are affected by LS and all carry the PTPN11 mutation c.836A > G (p.Tyr279Cys), identified by next-generation sequencing, while exhibiting different phenotypes.
Keywords: LEOPARD syndrome; PTPN11; multiple lentigines